Penerapan Insenerator Sederhana untuk Meningkatkan Kebersihan Desa Lubuk Batu Tinggal - Agus Prima Aspa; Eggi Sita Sunaria; Fauzan Azhiman; Ramses Iwan Situmorang; Riski Alzakry Ramadhan; Widya Khairani; Merianti M; Zahkiya Putri Effendi; Cindi Marcela; Ira Nur’ain (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Household waste management remains an environmental challenge in rural communities. Limited waste management facilities may lead to waste accumulation in certain areas and encourage uncontrolled open burning, which can adversely affect environmental quality. This community service activity aimed to implement a simple combustion facility as an effort to support residual waste management and improve environmental cleanliness in Lubuk Batu Tinggal Village. The implementation method consisted of environmental observation, identification of facility needs, site preparation, material preparation, installation of concrete culverts as a combustion chamber, construction completion, and activity evaluation. The activity was conducted through a participatory approach involving local community members in site preparation and facility construction. The results indicate that the construction of a simple combustion facility provided a more organized means of handling residual waste compared with irregular burning practices around residential areas. The facility also contributed to a more orderly environment and encouraged community participation in maintaining cleanliness. Its implementation should be accompanied by waste segregation and proper supervision to prevent recyclable or reusable materials from being burned and to ensure that the facility is operated with attention to safety and environmental considerations